P455 Awareness, knowledge and willingness to use HIV PrEP among MSM and TG people in bali, indonesia. (14th July 2019) - Umboh, Lucyan; Romyco, Irvin
Abstract : Background: World Health Organisation in 2014 has recommended Pre-Exposure Prophylaxis (PrEP) as HIV prevention tool for men who have sex with men (MSM) along with other prevention strategies. Before PrEP implementation is introduced in Indonesia, it is vitally important to have an evidence base about the awareness, knowledge and acceptability among MSM and transgender people and the differences in knowledge and PrEP acceptability based on sexual risk factors of MSM and transgender people. Methods: A cross-sectional study was conducted between July and November 2017 in an MSM clinic in Denpasar, Bali, Indonesia. The key outcomes were exploring the awareness, knowledge and willingness to use PrEP among MSM and transgender people in Bali, Indonesia and determining demographic and sexual risk factors associated with knowledge and willingness to use PrEP. Results: A total of 164 participants were recruited into the study but only 124 participants were eligible and included in the analysis. Of these, 69 out of 124 (55.6%) participants had never heard about PrEP. Among those 55 (44.4%) participants who had heard about PrEP, education and occupation were the only factors associated with PrEP knowledge. Men with the University education showed higher knowledge scores (29.2) and were more likely to use PrEP compared with men with lower education levels. 73 out of 124 participants (58.9%) were willing to take PrEP in the future and education was the only factor associated with PrEP willingness. Conclusion: This is the first study to report data on awareness, knowledge and willingness to use PrEP in Bali and is only the second such study conducted in Indonesia. Consistent with similar studies in other countries, this study found limited knowledge of PrEP among MSM and transgender participants. As PrEP is not yet publicly available in Indonesia, it is crucially important to prepare the community by education and disseminating accurate information. Disclosure: No significant relationships.